Characteristics and Pharmacological Regulation of Epithelial Na+ Channel (ENaC) and Epithelial Na+ Transport - Yoshinori Marunaka (Elsevier, 2014)
Epithelial Na+ transport participates in control of various body functions and conditions: e.g., homeostasis of body fluid content influencing blood pressure, control of amounts of fluids covering the apical surface of alveolar epithelial cells at appropriate levels for normal gas exchange, and prevention of bacterial/viral infection. Epithelial Na+ transport via the transcellular pathway is mediated by the entry step of Na+ across the apical membrane via Epithelial Na+ Channel (ENaC) located at the apical membrane, and the extrusion step of Na+ across the basolateral membrane via the Na+,K+-ATPase located at the basolateral membrane. The rate-limiting step of the epithelial Na+ transport via the transcellular pathway is generally recognized to be the entry step of Na+ across the apical membrane via ENaC. Thus, up-/down-regulation of ENaC essentially participates in regulatory systems of blood pressure and normal gas exchange. Amount of ENaC-mediated Na+ transport is determined by the number of ENaCs located at the apical membrane, activity (open probability) of individual ENaC located at the apical membrane, single channel conductance of ENaC located at the apical membrane, and driving force for the Na+ entry via ENaCs across the apical membrane. In the present review article, I discuss the characteristics of ENaC and how these factors are regulated. Keywords:: epithelial Na+ channel (ENaC), epithelial Na+ transport, chloride ion, electrophysiology, epithelium